ANALISIS PERBEDAAN KINERJA KEUANGAN BANK SYARI’AH DAN BANK KONVENSIONAL (Studi Kasus Pada Bank Muamalat Syariah dan Bank Negara Indonesia Periode 2012-2015) - Jusuf Al Fahmi; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTBank is one of the financial institutions used as finance, very vulnerable tothe conditions and roles in the country's economic growth. Observation of bankfinancial statements to find out the bank's information. This research aims tocompare the financial performance of Conventional Banking and Islamic Bankingin the period of 2012-2015 using the financial ratios of CAR, NPL, ROA, ROEand LDR.Methods of data retrieval in this study obtained from the financial statementsof each bank that officially use the bank's official website. Data analysis techniqueused is Independent Test T-Test method.Data analysis performed shows that there are significant differences in eachfinancial ratios. Conventional banks better perform their financial performance interms of CAR, NPL, ROA and ROE ratios. Islamic Banking is better in terms ofLDR ratio only.For researchers it is possible to increase the number of variations andperiods.Keywords : Conventional Banking; Islamic Banking; CAR; NPL; ROA; ROE andLDR